Radio activism : breaking the silence and empowering women - Rimmer, Annette; Radio Research Group (Manchester, England) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This unique book draws on the narratives of women participants in community radio, using intersectionality, feminist, critical psychological and community development frameworks to explore how this highly symbolic, creative dimension of activism can unmute marginalised women and enrich corporate media. Over a period of four years, twelve female radio project volunteers offer their experiences which they analyse, together as part of the RRG (Radio Research Group), alongside a conceptual and contextual framework to produce insights on the gendered nature of silence, voice and empowerment, and the wider potential of radio activism. Employing literature from a variety of fields, from bell hooks to Stuart Hall, the book foregrounds evidence from the majority world to argue the empowerment potential of community radio and the barriers to radio participation. Through this analysis community radio emerges as a site of development, from which diverse identities transpire/surface? through laughter, dialogue, raised consciousness and solidarity, but it also exposes the conflicts of empowerment by recognising inherent tensions in womanhood and in communities. Centering on the global, hegemonic challenge of empowering women, and relevant across multiple disciplines and professions, this is fascinating reading for academics, students and professionals in psychology, gender studies, media studies, development and related areas"--
The Radio Research Group -- Listen up! Radio's potential explored -- Radio training : feminist pedagogy in action -- Silence and voice -- Radio activism : dancing in the kitchen -- Feeling ten feet tall -- The mythical Sankofa bird, looking back and imagining the future.
Keywords: Radio Research Group (Manchester, England); Community radio -- Great Britain; Women in radio broadcasting -- Great Britain; Radio broadcasting -- Social aspects -- Great Britain; Feminism -- Great Britain; PSYCHOLOGY / General; PSYCHOLOGY / Social Psychology; PSYCHOLOGY / Mental Health